BYRON’S PERSONAL INVOLVEMENT IN POLITICAL REVOLUTIONS AND HOW HIS POETRY REFLECTS THE STRUGGLE FOR FREEDOM AND JUSTICE - Ruzibayeva Aziza Kahramanovna (The Conference Hub, 2025)
This article explores the themes of exile and alienation that are prevalent in Byron's poetry. Byron's personal life, marked by self-imposed exile and social exclusion, profoundly influenced his literary works, where he often portrayed an alienated person struggling with loneliness, identity, and longing. Through a detailed analysis of the poet's poems, the study highlights how Byron's attitude to exile goes beyond physical displacement to encompass emotional and psychological separation, reflecting broader Romantic concerns with individuality and freedom.
Keywords: Lord Byron, exile, alienation, romanticism, stranger, identity.